Thermophilic fungi as new sources for production of cellulases and xylanases with potential use in sugarcane bagasse saccharification - Cassia Pereira, J. de [UNESP]; Paganini Marques, N. [UNESP]; Rodrigues, A. [UNESP]; Brito de Oliveira, T. [UNESP]; Boscolo, M. [UNESP]; Silva, R. da [UNESP]; Gomes, E. [UNESP]; Bocchini Martins, D. A. [UNESP] (Wiley-Blackwell, 2015)
AimsTo obtain new cellulases and xylanases from thermophilic fungi; evaluate their potential for sugarcane bagasse saccharification.Methods and ResultsThirty-two heat-tolerant fungi were isolated from the environment, identified (morphological/molecular tools) and the production of the enzymes was evaluated by solid state fermentation using lignocellulosic materials as substrates. Myceliophthora thermophila JCP 1-4 was the best producer of endoglucanase (35751Ug(-1)), -glucosidase (4542Ug(-1)), xylanase (93111Ug(-1)) and avicelase (358Ug(-1)). These enzymes were most active at 55-70 degrees C and stable at 30-60 degrees C. Using crude enzymatic extract from M.thermophila JCP 1-4 to saccharify sugarcane bagasse pretreated with microwaves and glycerol, glucose and xylose yields obtained were 156 and 3513% (22 and 195g l(-1)), respectively.ConclusionsAll isolated fungi have potential to produce the enzymes; M.thermophila JCP 1-4 enzymatic extract have potential to be better explored in saccharification experiments. Pretreatment improved enzymatic saccharification, as sugar yields were much higher than those obtained from in natura bagasse.Significance and Impact of the StudyMyceliophthora thermophila JCP 1-4 produces avicelase (not commonly found among fungi; important to hydrolyse crystalline cellulose) and a -glucosidase resistant to glucose inhibition, interesting characteristics for saccharification experiments.
Keywords: enzymatic saccharification; glycerol; heat-tolerant fungi; microwaves; pretreatment